Aplicación del principio de proporcionalidad en las sanciones impuestas por la Supercom en el marco de la Ley Orgánica de Comunicación (LOC) a los medios privados de comunicación del Ecuador - Quezada Morocho, María Belén. (2016)
A permanent legal debate is summarized around considered disproportionate fines established in the Organic Law of Communication; which not only affect the economic right of the media but also affect the freedom of expression and freedom of the press, that at the rate that fines constitute a limitation to freely express information obtained by the media for fear to be punished. In this sense the Communications Law, enacted in 2013 contravenes the principle of proportionality in setting fines fixed ranges, which do not give the possibility to weigh and assess the characteristics of the media and the level of compliance with the standard, for illustrate this situation there is the case of breach of distributing music content and advertising space which are sanctioned with 10 Wages Basic Unified, regardless of the degree of non-compliance with the standard. In this situation you should consider the inclusion and assessment of the general principles of law which constitute ontological sense the cause and the basis of law, and are the central supports of the whole system which lend meaning. For this reason, it is inconceivable that a legal standard the contrary, because they exist independently of its legal or judicial recognition. In this regard, the principle of proportionality lies in the materialization of standards containing structure principles colliding fundamental rights, and their application is typical of the constitutional rule of law. - 5 - Therefore to conceive the Ecuador as a constitutional State of rights and justice and include in its rules a system of principles and guarantees that supply to all citizens in protecting their rights before a possible excess of power. It is recognized that the principles are an orientation for all public authorities for help, acting as a key to the correct application of constitutional principles, of great importance in administrative law, guidelines and means for the same, an essential pillar in the prohibition of arbitrary action of public authorities and in achieving legal certainty. Finally it is recognizing the imperative need to be carried out a reform that changes the range of sanctions contained in the Communications Law and through them to solve the problem of disproportionality of administrative sanctions.